Extraction optimization of phenolic compond from Zingiber Aromaticum Rhizome using pressurized hot water extraction (PHWE) - Asma’ Hannani, Ahmad Daud (Universiti Malaysia Perlis (UniMAP), 2014)
Access is limited to UniMAP community.